FLIGHT SAFETY MANAGEMENT PROBLEMS AND EVALUATION OF FLIGHT SAFETY LEVEL OF AN AVIATION ENTERPRISE - B. V. Zubkov; H. E. Fourar (Научный вестник МГТУ ГА)
This article is devoted to studying the problem of safety management system (SMS) and evaluating safety level of an aviation enterprise.This article discusses the problems of SMS, presented at the 41st meeting of the Russian Aviation Production Commanders Club in June 2014 in St. Petersburg in connection with the verification of the status of the CA of the Russian Federation by the International Civil Aviation Organization (ICAO) in the same year, a set of urgent measures to eliminate the deficiencies identified in the current safety management system by participants of this meeting were proposed.In addition, the problems of evaluating flight safety level based on operation data of an aviation enterprise were analyzed. This analysis made it possible to take into account the problems listed in this article as a tool for a comprehensive study of SMS parameters and allows to analyze the quantitative indicators of the flights safety level.The concepts of Acceptable Safety Level (ASL) indicators are interpreted differently depending on the available/applicable methods of their evaluation and how to implement them in SMS. However, the indicators for assessing ASL under operational condition at the aviation enterprise should become universal. Currently, defined safety levels and safety indicators are not yet established functionally and often with distorted underrepresented models describing their contextual contents, as well as ways of integrating them into SMS aviation enterprise.The results obtained can be used for better implementation of SMS and solving problems determining the aviation enterprise technical level of flight safety.